PENERAPAN METODE TEAM TEACHING PADA MATERI IKATAN KIMIA UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS X SMAN 9 TUNAS BANGSA BANDA ACEH - Latifah Hanum (FKIP USK, 2013)
This descriptive qualitative study aims to determine the activities of students and teacher as well as the ability to improve student learning outcomes through the implementation of team teaching method in the concept of chemical bonds. The subjects were 32 students of class X-1 SMAN 9 Tunas Bangsa Banda Aceh consisting of 18 female and 14 male. The data was collected through observation of students’ activity and teacher’s activity in implementing team teaching methods as well as providing a test at the end of the meeting. Data obtained from the observation suggests that the activity of students at each meeting (1st, 2nd and 3rd) increase significantly at 66.07%, 76.79% and 87.5%. Based on the observation, the ability of teachers in the implementation of team teaching increased from 73.44% in first meeting to 81.25% in the second meeting and 90.63% in the third meeting. Learning outcomes of students also increased as follows 62.5% (1st meeting), 81.25% (2nd meeting) and 93.75% (3rd meeting). Based on the results of study, it is can be concluded that the implementation of team teaching method can improve learning outcomes as well as student activity and the ability of teachers to implementing instructional material in the chemical bonds at SMAN 9 Tunas Bangsa Banda Aceh